2006
DOI: 10.1159/000088681
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life in Community-Dwelling Men with Pneumoconiosis

Abstract: Background: There have been few data on the health-related quality of life (HRQOL) in patients with pneumoconiosis. HRQOL is an important aspect of daily living in patients with industrial diseases. Objectives: To investigate the HRQOL and factors that contribute to the impairment of HRQOL in patients with pneumoconiosis. Methods: 297 patients with pneumoconiosis were recruited from a community-based case registry. The HRQOL was measured with the St. George’s Respiratory Questionnaire (SGRQ). Pulmonary functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
18
2
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 43 publications
3
18
2
4
Order By: Relevance
“…Previous studies in patients with pneumoconiosis and other chronic respiratory diseases revealed that these diseases had affected the quality of life of patients. Our results accord with these findings (3,14,23,24).…”
supporting
confidence: 93%
See 3 more Smart Citations
“…Previous studies in patients with pneumoconiosis and other chronic respiratory diseases revealed that these diseases had affected the quality of life of patients. Our results accord with these findings (3,14,23,24).…”
supporting
confidence: 93%
“…These results indicate that silicosis patients have more severe depressive symptoms than the controls. Psychiatric disorders were found to be more frequent in patients with pneumoconiosis than in the normal population in a study which focused on the relationship between silicosis and depression (23). It has been established that elderly silicosis patients have high rates of depression co-morbidity (3,25).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The SGRQ has been validated for use in Chinese patients with chronic obstructive pulmonary disorder (COPD) 18 and in Hong Kong Chinese patients with pneumoconiosis. 8 The symptom and activity components of the questionnaire were used to measure symptom and activity impairment on a scale ranging from 0 to 100, where 0 represents the best health status. 19 …”
mentioning
confidence: 99%